USING REALISTIC MATHEMATICS EDUCATION IN MATHEMATICAL PROBLEM-SOLVING ABILITY BASED ON STUDENTS’ MATHEMATICAL INITIAL ABILITY - Ilma Nurfadilah; Hepsi Nindiasari; Abdul Fatah (Prima: Jurnal Pendidikan Matematika, 2021)
The 2013 curriculum requires students to master the cognitive domains from analysis to evaluation. The fact is not all students have the same cognitive development. Junior high school students, it turns out that students who think concretely, must see in real terms, so the learning approach used in this study has to lead students to be active in learning. One of active learning approach is the Realistic Mathematics Education (RME). This study is an experimental research. The goals of this study are: 1. Is the mathematical problem-solving abilities of students who used the RME approach better than students who used the scientific approac? 2. Determine whether there is an interaction between the learning approach and the mathematical initial ability (high, medium, low) on students' mathematical problem-solving abilities. The results showed: 1. The mathematical problem-solving abilities of students who used the RME approach was better than students who used the scientific approach; 2. There is no interaction between the learning approach and mathematical initial abilities (high, medium, low) on students' mathematical problem-solving abilities.